The genus Eluma in the Iberian Peninsula, with the description of a new terrestrial isopod: Eluma matae sp. nov. (Oniscidea, Armadillidiidae, Eluminae) - Cifuentes, Julio; da Silva, Luis P. (European Journal of Taxonomy, 2023)
The genus Eluma Budde-Lund, 1885, was composed until now by three species, with a Betic-Rif distribution type. In this work a new species of the genus is described, Eluma matae sp. nov., from the West region of Portugal. The distribution of the two other known species present in the Iberian Peninsula is updated, and figures of the three Iberian species are provided to facilitate their identification. Finally, a dichotomic key for the entire Eluma genus was also created.